Textile-Based Flexible Pressure Sensors: A Review - Zhang, Jia-wen; Zhang, Yan; Li, Yuan-yuan; Wang, Ping (Polymer reviews, 2022)
This paper provides a review of recent developments in the rapidly changing and advancing field of textile-based flexible pressure sensors. It summarizes the basic principles and approaches employed when building textile-based pressure sensors as well as the most commonly used materials and techniques. The textile pressure sensor is a promising candidate for the next-generation sensing platform since it can be easily incorporated into modern garments in a breathable and conformable way. This article briefly introduces the characteristics of piezoelectric, capacitance, piezoresistive and triboelectric flexible pressure sensors, focuses on the working principles of these four types of flexible pressure sensors and reviews their recent progress and applications in electronic skin, health care and rehabilitation, human motion capture, physiological activity monitoring and human-machine interaction. Moreover, the remaining challenges in the development process and prospects of textile-based flexible sensors are discussed.